HIV viral sequences in seronegative people at risk detected by in situ hybridisation and polymerase chain reaction. Issue 6675 (18th March 1989) - Pezzella, M.; Rossi, P.; Lombardi, V.; Gemelli, V.; Mariani Costantini, R.; Mirolo, M.; Fundaro, C.; Moschese, V.; Wigzell, H.
Abstract : A study was conducted to assess the occurrence of latent infection with the human immunodeficiency virus (HIV) among seronegative people at high risk of infection. The presence of HIV genomes was analysed by molecular techniques in two seronegative children born to mothers infected with HIV and in three regular sexual partners of seropositive drug addicts. The adults were selected from a seronegative cohort at high risk of infection because of their sexual contacts and the children selected because of impaired growth. HIV retroviral sequences were detected in four of the five subjects directly at the cellular level by in situ hybridisation in peripheral blood mononuclear cells. HIV genomic sequences were confirmed by in vitro amplification of viral DNA with the polymerase chain reaction technique. The existence of a latent viral infection state in these seronegative subjects indicates the unreliability of standard serological analysis in people who have been in regular contact with infected patients.